Cultivating environmental citizenship in teacher education. Issue 2 (2nd April 2016) - Green, Carie; Medina-Jerez, William; Bryant, Carol
Abstract : Research on environmental action projects in teacher education is limited. Furthermore, projects that emphasize the role of citizens and governments in environmental problem-solving are scarce. The purpose of this study was to explore how participating in a political environmental action project influenced pre-service teachers' environmental citizenship. Following the steps of Project Citizen, an international civic education program, pre-service teachers learned about and proposed policy solutions to address excessive energy usage at their university. Analysis revealed growth in the pre-service teachers' environmental citizenry, including their self-efficacy, values awareness, and ecological and civics literacy. Through critical appraisal of their local energy-yielding system, the pre-service teachers recognized energy conservation as a cultural problem with local and global implications, furthering their commitment to action-oriented environmental education.